Enhanced prognostic and immunomodulatory effects of novel cuproptosis-related long noncoding RNAs in wilms tumor - Yadong Li; Mingjie Li (Frontiers in Molecular Biosciences)
ObjectiveThis study aims to develop a model for long non-coding RNA (lncRNA) associated with cuproptosis and assess the efficacy of immunotherapy and chemotherapy in children with Wilms tumor (WT) based on individualized risk scores.MethodsData was obtained from the online database. Cox proportional hazards analysis and LASSO Cox regression were employed to generate cuproptosis-related lncRNA signatures. Patients were classified into high- and low-risk groups and clinical outcomes were further analysed. Tumor mutation burden and immunoinfiltration were calculated and potential immunotherapy response was evaluated. The sensitivity of immunotherapy and chemotherapy was ultimately analyzed based on individual risk scores associated with cuproptosis.ResultsA eight cuproptosis-related lncRNAs signature was established and high-risk group showed a worse prognosis than the low-risk group. This model showed a good diagnostic performance. Low-risk group displayed an elevated tumor immune dysfunction and was more sensitive to 13 drugs.ConclusionThe current study introduces a novel approach for predicting clinical prognosis and determining the appropriate therapy for patients with WT.